(untitled) (Baghdad Science Journal, 2022)
Two quantitative, environment-friendly and easily monitored assays for Ni (II) and Co (III) ions analysis in different lipstick samples collected from 500-Iraqi dinars stores located in Baghdad were introduced. The study was based on the reaction of nickel (II) ions with dimethylglyoxime (DMG) reagent and the reaction of cobalt (III) ions with 1-nitroso-2-naphthol (NN) reagent to produce colored products. The color change was measured by spectrophotometric method at 565 nm and 430 nm for Ni and Co, respectively, with linear calibration graphs in the concentration range 0.25-100 mg L-1 (Ni) and 0.5-100 mg L-1 (Co) and LOD and LOQ of 0.11 mg L-1 and 0.36 mg L-1 (Ni), and 0.15 mg L-1 and 0.49 mg L-1 (Co). The UV/VIS data was compared to the results obtained by a novel microfluidic paper-based analytical device (µPAD) platform offering in-situ and cost-effect assay with a similar calibration graph with LOD and LOQ of 0.21 mg L-1 and 0.70 mg L-1 (Ni), and 0.22 mg L-1 and 0.75 mg L-1 (Co). The analysis of variance (ANOVA) indicated no significant difference between the UV/VIS, µPAD, and standard atomic absorption spectrometry (AAS) assay Ftab= 3.46 is much higher than FStat = 0.13 (Ni) and Ftab= 3.46 is much higher than FStat = 0.02 (Co). Also, a good correlation between results via the three methods was found. Thus, the µPAD platform offers a solid base for providing valuable information outside centralized laboratories.